Introducing Ethanol Ablation as a treatment for thyroid cysts in the emergency setting. (1st March 2022) - Robb, Lydia; Hey, Shi Ying; Reid, Helen; Nixon, Iain
Abstract: Introduction: New techniques have been adopted for minimally invasive management of thyroid lesions which has been well explored by Nixon et al. Ethanol ablation (EA) for the treatment of thyroid cysts has been well documented in the literature as a safe, effective treatment option in the elective setting. Our unit has introduced this service in the elective setting for treatment of thyroid cysts. This study demonstrates the use of EA in the emergency setting, which has potential to reduce recurrence rates and avoid a general anaesthetic in patients who present acutely. Methods: Three patients presenting with airway threatening compressive symptoms secondary to thyroid cysts. Treated with EA within 24 hours of presentation to hospital. Patients were followed up radiologically and clinically and a telephone consultation to gather the GBI (Glasgow Benefit Inventory) survey. Results: 2 patients female and 1 male, median age of 41 years old. Median Pre-ablation cyst volume was 97.3mls. Median 100% radiological resolution of cystic component. 100% resolution of symptoms at median 9-month follow-up post procedure. 66% of patients requiring only one treatment for 100% resolution, with 1 patient with the largest cyst requiring three ablations and two aspirations. No complications reported. GBI (Glasgow Benefit Inventory) score mean +27.7, similar GBI of a tonsillectomy. Discussion: EA is a safe, cost effective and efficient treatment option for thyroid cysts in the acute setting. Larger thyroids cysts may require repeated procedures for symptom resolution. Patient will require long term follow up to assess the rate of recurrence.